Civil society and state practices in Egypt. Case studies: Innovation and civic education - Gaber, Rana (AUC Knowledge Fountain, 2017)
In this study, I explore the different factors enabling civil society in influencing state practices. And how this is reflected in the social and economic development of the state. I am mainly focusing on Egypt, specifically going through a comparative analysis of the different development strategies from Nasser till Al Sisy. In addition, drawing a comparison between Innovation and Civic Education as two case studies. The framework through which the dynamic state society relations are explored is Michael Mann's "Sources of Social Power" and Joel S. Migdal's "Strong Societies and Weak States". The different factors I identified were; political change, the purpose of the local civil society actors, as well as international support. The influence of these factors on state practices from recognition of civil society, support to civil society, and policy change. And thus, identifying the social and economic development of the state.